Between fear and hope : Sri Lankan refugees in Tamil Nadu - Suryanarayan, V.; Sudarsen, V., 1950-2005. (Chennai : T.R. Publications, 2000)
Highlights the refugee crisis with the need for enactment of a refugee law which reflects humanitarian concerns.
Keywords: Political refugees -- Sri Lanka; Tamil (Indic people) -- Sri Lanka